A STUDY TO ASSESS SCHOLASTIC BACKWARDNESS IN THIRD STANDARD STUDENTS AT AN ASHRAM SCHOOL IN NAVI MUMBAI. - DR. VINOD S. KAMBLE; DR. APARNA Y. TAKPERE (International Journal of Pharma and Bio Sciences, 2013)
Overall prevalence of scholastic backwardness was 59.40% when the average of all the skills was taken. 60 (76.92 %) were below average in the reading skill, 34 (43.59 %) students in mathematical calculation skill and 45(57.69 %) students in mathematical problem solving skill. Using Kruskal-Wallis test for Table no.1 and 2, it was found that there was no significant variation in the performance between the students when tested for the skills of 1) basic reading, 2) mathematical calculation and 3) mathematical reasoning with respect to the scores given for the skills. Kw=0.03519, p=0.9826. Using Mann Whitney Test it was observed that there was no significant difference between male and female students, U=9.000, p=0.5296 with respect to the performance scale. 59.04% of the students scored below average. Hence there is need to change the way of teaching but no need of any special educator or any special therapy. 59.04% students are scholastically backward but there is no Learning Disability amongst them.